(untitled) (Ustozlar uchun, 2025)
The Progress in International Reading Literacy Study (PIRLS) is a well-known international assessment that measures the reading literacy of fourth-grade students around the world. It focuses not only on basic reading skills, but also on how effectively students understand, interpret, and think critically about written texts. Despite continuous reforms in education, PIRLS results show that many students experience difficulties with deeper comprehension tasks, especially those requiring inference and evaluation. This article discusses PIRLS in a clear and human-centered academic style, identifies a key problem related to weak higher-order reading comprehension skills, examines its main causes, and suggests practical solutions that can realistically be applied in primary classrooms. The purpose of this paper is to highlight how improving everyday teaching practices can lead to better reading outcomes and stronger PIRLS performance.